FAN score predicts prognosis after platinum-based first-line chemotherapy in patients with metastatic urothelial carcinoma - Yu Ishizuya; Atsunari Kawashima; Yuki Horibe; Akinaru Yamamoto; Masaru Tani; Akihiro Yoshimura; Liu Yutong; Sassi Nesrine; Toshiki Oka; Yohei Okuda; Toshihiro Uemura; Gaku Yamamichi; et al. (Scientific Reports)
Abstract We have reported that the FAN score, which consists of the fibrosis-4 (Fib-4) index, albumin–bilirubin (ALBI) score, and neutrophil–lymphocyte ratio (NLR), is a prognostic marker for patients receiving pembrolizumab for mUC. However, it remains unclear whether the FAN score is a prognostic factor for platinum-based first-line chemotherapy. We included 126 patients with mUC who received platinum-based first-line chemotherapy. The median PFS and overall survival (OS) were 6.3 months (95% confidence interval [CI] 4.5–8.0) and 14.0 months (95% CI 11.1–16.9), respectively. Multivariable analysis showed that Fib-4 index (HR 3.85, 95% CI 1.09–13.58, p = 0.036), ALBI score (HR 1.53, 95% CI 1.01–2.31, p = 0.045), and NLR (HR 1.76, 95% CI 1.14–2.71, p = 0.010) were independently associated with PFS. The FAN score was also associated with PFS (HR 2.56, 95% CI 1.62–4.05, p < 0.001). The median PFS for patients with low FAN score (≤ 1) and those with high FAN score (≥ 2) were 7.8 (95% CI 5.0–9.0) months and 3.0 (95% CI 1.6–5.8) months, respectively. In conclusion, the FAN score is a prognostic factor for mUC patients who are treated with platinum-based first-line chemotherapy.